Contributi Italiani al XV Congresso Internazionale degli Slavisti (Minsk, 20-27 agosto 2013) - Garzaniti, Marcello; Alberti, Alberto; PEROTTO, MONICA; SULPASSO, Bianca (Biblioteca di Studi Slavistici, 2013)
This volume contains Italian contributions to the XV Slavists' International Congress (Minsk, 20-27 August 2013). In the wake of the best Italian Slavic tradition, the lecturers present a wide range of themes in different languages, ranging from the Cyril-Methodian question to the critical reflection on contemporary authors. Despite the diversity of disciplinary and methodological approaches - from paleography to textual analysis, from literary comparative studies to sociolinguistics - these contributions show that Italian Slavistic studies maintains their roots, critically developing previous studies and opening up new perspectives for research, while a new generation of scholars is born. As in the past, Italian studies on Slavistics are playing a significant role not only in Italy's cultural relations with the Slavic countries, but more generally on the perspective of a vast and complex process of integration of the various European cultures, which goes further beyond the borders of the European Union; a process in which the Slavic world, with its variety of languages and cultures, is one of the main actors.